Arabidopsis ZINC FINGER PROTEIN1 Acts Downstream of GL2 to Repress Root Hair Initiation and Elongation by Directly Suppressing bHLH Genes. Issue 1 (15th November 2019) - Han, Guoliang; Wei, Xiaocen; Dong, Xinxiu; Wang, Chengfeng; Sui, Na; Guo, Jianrong; Yuan, Fang; Gong, Zhizhong; Li, Xuezhi; Zhang, Yi; Meng, Zhe; Chen, Zhuo; et al.
Abstract : A C2H2-type zinc finger protein gene containing an EAR motif inhibits root hair initiation and elongation by suppressing the expression of genes known to play important roles in root hair initiation and elongation. Abstract: Cys2His2-like fold group (C2H2)–type zinc finger proteins promote root hair growth and development by regulating their target genes. However, little is known about their potential negative roles in root hair initiation and elongation. Here, we show that the C2H2-type zinc finger protein named ZINC FINGER PROTEIN1 (AtZP1), which contains an ERF-associated amphiphilic repression (EAR) motif, negatively regulates Arabidopsis ( Arabidopsis thaliana ) root hair initiation and elongation. Our results demonstrate that AtZP1 is highly expressed in root hairs and that AtZP1 inhibits transcriptional activity during root hair development. Plants overexpressing AtZP1 lacked root hairs, while loss-of-function mutants had longer and more numerous root hairs than the wild type. Transcriptome analysis indicated that AtZP1 downregulates genes encoding basic helix-loop-helix (bHLH) transcription factors associated with root hair cell differentiation and elongation. Mutation or deletion of the EAR motif substantially reduced the inhibitory activity of AtZP1. Chromatin immunoprecipitation assays, AtZP1 :glucocorticoid receptor (GR) induction experiments, electrophoretic mobility shift assays, and yeast one-hybrid assays showed that AtZP1 directly targets the promoters of bHLH transcription factor genes, including the key root hair initiation gene ROOT HAIR DEFECTIVE6 ( RHD6 ) and root hair elongation genes ROOT HAIR DEFECTIVE 6-LIKE 2 ( RSL2 ) and RSL4, and suppresses root hair development. Our findings suggest that AtZP1 functions downstream of GL2 and negatively regulates root hair initiation and elongation, by suppressing RHD6, RSL4, and RSL2 transcription via the GL2/ZP1/RSL pathway.